In vitro determination of efficacy of indigenous plant extracts used for internal parasites control by small-holder livestock farmers in Chief Albert Luthuli Municipality, Mpumalanga Province, South Africa - Shiba, Mlungisi Richard (My University, 2018)
Ethno veterinary medicine practices are popular among the resource constrained small-holder farmers. Nonetheless, the effectiveness of traditional remedies particularly the indigenous plants has not been extensively documented. Hence, this study was conducted to determine efficacy of indigenous plant extracts used by small-holder farmers in Chief Albert Luthuli Local Municipality, Mpumalanga Province, South Africa for internal parasites control. Information on indigenous plants used for the control of internal parasites of livestock by local farmers in the study area was gathered through a questionnaire survey. A total of 188 livestock farmers (both males and females) of mixed ages were interviewed. Thirteen different plants were frequently mentioned by the respondents as remedies for livestock internal parasites. Of these, seven plants could be identified up to their families and species. Plant species collected were Dicerocaryum sp (50%), Pappeacapensis (61%), Aloe ferox (90%), Helichrysum sp (56%), Senecio congestus (83%), Senecio barbertonicus (67%) and Gardenia sp (73%). These plants were extracted using distilled water and analysed to determine their efficacy through in vitro assays; Egg hatch, larval development and larval mortality assays. All the assays were performed at different concentrations of 2.5mg/ml, 5.0mg/ml and 7.5mg/ml. The nematode third stage larvae were incubated for 24hr, 48hr and 72hr during the larval mortality assay. The present study showed that all the seven-plant species under investigation possessed some anthelmintic activities of varying strength. The highest egg hatch inhibition was observed from the extracts of Senecio barbertonicus with 100 % and the lowest from Dicerocaryum eriocarpum with 2.25 %, for larval development the highest was Gardenia sp 100 % and the lowest Helichrysum sp 26 % at concentration 7.5 mg/mL respectively. Whereas, the highest in larval mortality assay was Senecio barbertonicus and Gardenia sp achieved 100 % after 48hrs and the lowest was Dicerocaryum eriocarpum with49.89 % after 72hrs at concentration 7.5 mg/mL respectively. The use of other different forms of extraction media is recommended because different results can observe and be compared with the results of the present study. Toxicity studies on the indigenous plants observed to have stronger anthelmintic activities would assist in the future recommendation of these remedies for large scale or commercial use as anthelmintic drugs. Keywords: ethno veterinary medicine, gastrointestinal parasites, anthelmintic
Thesis (M. Agricultural Management (Animal Production)) -- University of Limpopo, 2018
Keywords: Ethno veterinary medicine; Gastrointestinal parasites; Anthelmintic; Animals -- Diseases -- Control; Traditional medicine; Veterinary medicine; Livestock -- Parasites